Food flow analysis: the role of locality in feeding cities [Abstract only] - Karg, H.; Akoto-Danso, Edmund K.; Schlesinger, J.; Nyarko, G.; Drechsel, Pay (2015)
The growing urban demand for food and changing diets are two of the main factors for changing urban food systems in terms of food quantity and diversity, as well as underlying production and distribution systems. In order to meet the urban food needs while minimising negative environmental effects, short supply chains have been advocated in recent years. In spite of the growing attention to “local” or “urban“ food in research and development, there are only very few empirical studies which systematically analyse the actual contribution of urban and periurban production to urban food supply in a standardised way. This study as part of two PhD projects aims to quantify and map food flows supplying urban populations in the cities of Tamale, Ghana and Ouagadougou, Burkina Faso, both cities that are characterised by high urban growth rates and high incidences of food insecurity. Food flows were recorded at roads entering the cities and at major markets during the peak and lean season. Data collection will extend over two years, and therefore only first preliminary results are available so far (Tamale for the peak season 2013, and lean season 2014; Ouagadougou for the lean season 2014). First results show that in both cities the majority of unprocessed staple crops are produced in rural areas and channelled through village markets to the cities while leafy vegetables are produced during the dry season in irrigated urban and peri-urban agriculture (UPA). In Tamale, imports play a minor role: rice is the only food crop imported at large scale from outside Africa (preliminary results indicate that about half of the rice consumed in both cities is imported), whereas sub-regional trade plays a role with respect to onion (from Niger) and tomato supply (from Burkina Faso during the lean season). Ouagadougou’s status as national capital is reflected in the larger diversity of food items in the markets and the relatively longer distances (partly imported) food travels. The two case studies suggest that diversifying food sources can be a means to minimise risks and to ensure access to favourable market prices which contributes to a more resilient urban food supply system. This might change with increasing economic status and growing city size, when creating space for UPA and supporting rural small holders will become more important to maintain the mix.